2018
DOI: 10.1002/cbin.11071
|View full text |Cite
|
Sign up to set email alerts
|

miR‐381 overcomes cisplatin resistance in breast cancer by targeting MDR1

Abstract: Increasing evidence suggests the involvement of microRNA-381 (miR-381) in chemoresistance of cancer treatment. However, its function and molecular mechanisms in breast cancer chemoresistance are still not well elucidated. In the present study, we aimed to investigate the functional role of miR-381 in cisplatin (DDP) resistance of breast cancer and discover the underlying molecular mechanism. The expression levels of miR-381 and MDR1 were detected by quantitative real-time PCR (qRT-PCR) and Western blot analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…38 A recent study reported that miR-381 could overcome CDDP resistance in breast cancer through directly inhibiting MDR1. 20 Correspondingly, our found indicated that miR-381 overexpression overcame CDDP resistance in MCF-7/ CDDP and MDA-MB-231/CDDP cells. Additionally, miR-381 inhibition reversed EZH2 knockdown-mediated enhancement of CDDP sensitivity in MCF-7/CDDP and MDA-MB-231/CDDP.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…38 A recent study reported that miR-381 could overcome CDDP resistance in breast cancer through directly inhibiting MDR1. 20 Correspondingly, our found indicated that miR-381 overexpression overcame CDDP resistance in MCF-7/ CDDP and MDA-MB-231/CDDP cells. Additionally, miR-381 inhibition reversed EZH2 knockdown-mediated enhancement of CDDP sensitivity in MCF-7/CDDP and MDA-MB-231/CDDP.…”
Section: Discussionsupporting
confidence: 58%
“…19 Recently, miR-381 was reported to overcome CDDP sensitivity in breast cancer through targeting MDR1. 20 All these studies suggested that miR-381 was closely implicated with cancer chemoresistance. However, how miR-381 was regulated in breast cancer is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similar trends have also been previously in miR-124-3p [22] and miR-203a [23]. As for miR-381, it has been particularly suggested to play critical functions in overcoming cisplatin resistance in breast cancer treatment [24][25][26].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, recent studies have shown that miR-381 has a very important role in tumor oncogenesis, development, metastasis and chemical resistance. For example, miR-381 inhibits the proliferation and invasion of prostate cancer cells via the regulation of UBE2C [41]; miR-381 inhibits lung adenocarcinoma progression by directly targeting LMO3 through the regulation of the PI3K/Akt signaling pathway and EMT [42]; up-regulation of miR-381 inhibits the NAD + salvage pathway and promotes apoptosis in breast cancer cells [43]; miR-381 overcomes cisplatin resistance in breast cancer cells by targeting MDR1 [44]. In line with these findings, metformin upregulated the level of miR-381 to inhibit NSCLC tumor growth and metastasis in our study.…”
Section: Discussionmentioning
confidence: 99%